Prevalence of diseases by canine blood parasites in Companion Veterinary Clinic, Melaka, Malaysia - Ying, Megan Chan Zhi; Wijaya, Agus; Afiff, Usamah (ARSHI Veterinary Letters, 2023)
A disease caused by canine blood parasites (tick-borne diseases) is a condition in which dogs are bitten by tick-carrying pathogens. This study assessed the prevalence of diseases caused by canine blood parasites (Anaplasmosis, Babesiosis, and Ehrlichliosis) at the Companion Veterinary Clinic, Melaka, Malaysia, from August 2020 to July 2022. Secondary data of 103 infected dogs were obtained from medical records. Dogs at the puppy stage were more commonly diagnosed (26.21 %). Both males and females showed almost the same prevalence of 52.43% and 47.57%, respectively. Mongrel had a relatively higher prevalence compared to pedigree dogs but there was no breed predisposition. Multiple infections were more common than single infections. Canine tick-borne diseases show a higher prevalence during the intermonsoon season in Malaysia. Anorexia, inactivity, and bleeding diatheses are the most common clinical signs observed in dogs. To support the diagnosis, anaemia and thrombocytopenia were observed in the patient’s complete blood count results. The test kit was positive when antibodies or antigens were detected and parasites could also be observed under a microscope using a blood smear. The prevalence of tick-borne diseases is influenced by intrinsic (age and sex) and extrinsic factors (weather).